Production of HIV/AIDS lessons in the entertainment-education television programme Tsha Tsha and their reception by HIV-positive men in Soweto-Johannesburg - Ogenga, Fredrick Oduor (My University, 2008)
This study aims to examine the production of HIV/AIDS lessons on Tsha Tsha Entertainment-Education and their reception by HIV-positive men in Soweto, and to find out whether this response impacts on their perception of their roles and responsibilities in HIV/AIDS. The rationale behind this study is that gender and HIV/AIDS has been critical in interventions aimed at combating the disease. Studies in South Africa on gender have revealed that versions of masculinity can be implicated in the increasing infection rates of HIV/AIDS making efforts to combat the disease problematic. A qualitative methodology is used. This method included interviews and focus group discussions. Five interviews were done with programme producers and researchers of Tsha Tsha to find out the major considerations in production. An average of seven HIV-positive men were exposed to 12 episodes of Tsha Tsha to find out their responses in six focus group discussions, and whether these indicated a changed perceptions in their roles and responsibilities in HIV/AIDS. Their responses were then examined under Bandura’s (1971) social learning theory and Hall’s (1977) encoding-decoding theory .This theories explain the considerations in the production of lessons in Tsha Tsha and how audiences respond to those lessons respectively. The findings reveal that audiences (HIV-positive) men identify with lessons around HIV-testing, disclosure, support and those that challenge stigma and masculinity in HIV/AIDS. Disclosure emerges as a major theme and is compared with sub themes of testing, stigma, masculinity and social support to form categories that are presented as the findings. While HIV-disclosure is seen as challenging HIV/AIDS stigma and masculinity, where men accept their condition, and take responsibility to continue occupying their space as men, E-E production can reinforce lessons around disclosure and other coping strategies to combat HIV/AIDS.
Keywords: HIV/AIDS lessons; Tsha Tsha TV production; Entertainment-Education; HIV-positive men; stigma in HIV/AIDS; masculinity in HIV/AIDS; men; Soweto